DELIMITATIONS OF ECOLOGICAL INTERFACES IN BRAZIL: AN EVALUATION OF BIOMES AND ECOTONES (CIPEEX, 2025)
This study investigates the transition areas between biomes in Brazil, with an emphasis on the interfaces between the Cerrado and the Amazon. The research is motivated by the growing pressure on these regions, resulting from agricultural expansion and climate change, which intensify environmental degradation and biodiversity loss. Based on the studies by Aziz Ab'Saber, which highlighted the importance of ecotones in ecological connectivity, there is a need for robust methodologies for the precise delimitation of these areas. A literature review, covering classic and recent studies on biogeography, reveals methodological challenges in mapping biomes and ecotones. The next phases of the research will apply geospatial techniques, such as high-resolution satellite imagery, topographic and climate data, which are essential for identifying ecological transition patterns. Advanced remote sensing methods, such as NDVI, will be used to characterize transition zones. Preliminary results indicate that these areas are more dynamic and vulnerable than previously thought. The combination of geospatial data and interviews with experts will allow for a more refined analysis, highlighting subregions with unique ecological characteristics. The research also suggests the need for an interdisciplinary approach that incorporates climatic, geological, ecological, and anthropological factors in the delimitation of transition areas. Thus, the study will contribute significantly to the understanding of the complex interactions that shape the Brazilian biogeographic landscape, with direct implications for environmental planning and sustainable development in the country.
Keywords: Ecological transition; Remote sensing; Ecotones; Cerrado-Amazon